Transparent polylactic acid film with network crystal structure and preparation method thereof

By using EBH nucleating agent and solid-phase stretching technology in polylactic acid films, the network crystal structure is formed, and the problem of transparency deterioration after modification of PLA materials in the prior art is solved, and a combination of high transparency and excellent mechanical properties is achieved.

CN119708560AActive Publication Date: 2025-03-28SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411800652.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The prior art usually sacrifices its transparency when improving the heat resistance, toughness and other properties of polylactic acid (PLA) materials, resulting in a significant deterioration in the transparency of the modified PLA film.

Method used

By selecting specific N,N-ethylene bis(12-hydroxystearamide) (EBH) as the nucleating agent and combining solid phase stretching technology, a transparent polylactic acid film with a network crystal structure was prepared. Under the special solid phase stretch ratio, this method acts between PLA and EBH nucleating agent to form a unique network crystal structure, which improves the strength, heat resistance and toughness of the film while maintaining high transparency.

Benefits of technology

It achieves the strength, heat resistance and toughness of polylactic acid films without sacrificing transparency, and widens the application range of PLA materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708560A_ABST
    Figure CN119708560A_ABST
Patent Text Reader

Abstract

The invention provides a transparent polylactic acid film with a network crystal structure and a preparation method thereof, the preparation method comprises the following steps: mixing 95-99.5 parts by weight of PLA and 0.5-5 parts by weight of an EBH nucleating agent as a mixture, then sequentially carrying out screw melt extrusion granulation and hot press molding to obtain a sheet to be stretched, and finally carrying out hot press molding on the sheet to be stretched to obtain the transparent polylactic acid film with the network crystal structure. Finally, the sheet to be stretched is subjected to one-way or two-way solid-phase stretching treatment, and the transparent polylactic acid film with the three-dimensional crystal network structure is prepared. According to the preparation method, specific N, N-ethylidene bis (12-hydroxystearamide) is selected as a nucleating agent, and a solid-phase stretching technology is combined, so that the PLA film product with high transparency is prepared. Wherein exploration finds that a unique network crystal structure can be formed under the action between PLA and an EBH nucleating agent under a special solid-phase stretching rate, and a film product is endowed with excellent strength, heat resistance and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polylactic acid-based film materials, and relates to a transparent polylactic acid film with a network crystal structure and a preparation method thereof, and specifically to a method for preparing a polylactic acid film with super-strong, super-tough, heat-resistant and transparent properties by using polymer solid phase stretching technology. Background Art

[0002] Biodegradable polymer materials refer to polymer materials that can undergo chemical, biological or physical changes in chemical structure, main chain rupture, molecular weight reduction, and then form small molecular compounds under the action of microorganisms (bacteria, fungi, algae, etc.) or animal and plant tissue cells and enzymes in the natural environment, and eventually become small molecules such as water, carbon dioxide, and methane. They are non-toxic and harmless, can be completely absorbed by the environment, and are pollution-free. They have broad application prospects in the field of disposable plastic packaging products that need to be landfilled. Common synthetic biodegradable polymer materials mainly include aliphatic polyesters, polyester ethers, polyphosphazenes, polyorthoesters, polycarbonates, polyanhydrides, polyamino acids, etc. The varieties that can be industrially produced in my country currently include polylactic acid (PLA), copolymers of polybutylene adipate and polybutylene terephthalate (PBAT), polycaprolactone (PCL), polypropylene carbonate (PPC), polyglycolic acid (PGA), polyhydroxyalkanoates (PHA), dibasic acid and dibasic ester polymers, etc. Among them, PLA has excellent biodegradability, biocompatibility, and mechanical properties, and the raw material lactic acid comes from biomaterials such as starch and cellulose, making it the mainstream of biodegradable plastic products. However, there is only one methylene carbon atom between the ester groups on the PLA main chain, and the short and rigid repeating units make its molecular chain helical, with a slow crystallization rate. It almost does not crystallize during the extrusion, injection molding and other molding processes, resulting in a long molding cycle, low heat deformation temperature, and limited application range.

[0003] At present, in order to improve the above-mentioned shortcomings of PLA materials, researchers focus on the modification research of PLA itself, but most of the research aims to improve a specific performance alone, such as improving the heat resistance and toughness of PLA through modification; on the other hand, by adding fillers, blending systems or reinforcement systems to improve the comprehensive performance of PLA-based composite materials, further broadening the application scope of PLA materials.

[0004] However, the above-mentioned existing technologies and process means for improving PLA materials will inevitably sacrifice the transparency of PLA products, especially PLA films, resulting in a significant deterioration in transparency after modification of PLA. In the method of adding fillers, the transparency of the final product depends greatly on the selection of fillers. At the same time, the processing aids required in the blending system or the reinforcement system will also lead to a significant deterioration in the transparency of the product.

[0005] Therefore, there is an urgent need to develop a polylactic acid film with excellent comprehensive performance and good transparency and its preparation process, which will be very important for expanding the application field of PLA. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention provides a transparent polylactic acid film with a network crystal structure and a preparation method thereof. The preparation method selects a specific N, N-ethylenebis (12-hydroxystearamide) (N, N-Ethylenebis-(12-hydroxystearamide), EBH) as a nucleating agent and combines it with a solid phase stretching technology to prepare a PLA film product with high transparency. It is found that under a special solid phase stretching ratio, the interaction between PLA and the EBH nucleating agent can form a unique network crystal structure, which gives the film product excellent strength, heat resistance and toughness.

[0007] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0008] The present invention provides a method for preparing a transparent polylactic acid film having a network crystal structure, which mainly comprises the following steps:

[0009] (1) The raw materials mainly including the following components are mixed and prepared as a mixed material by weight:

[0010] PLA 95-99.5 parts,

[0011] EBH nucleating agent 0.5-5 parts,

[0012] The polylactic acid and EBH nucleating agent totaled 100 parts;

[0013] (2) subjecting the mixed material prepared in step (1) to melt extrusion granulation and hot pressing molding in sequence to prepare a sheet to be stretched for a film product;

[0014] (3) subjecting the sheet to be stretched obtained in step (2) to uniaxial or biaxial solid phase stretching to prepare a transparent polylactic acid film having a network crystal structure;

[0015] The process parameters of the unidirectional solid phase stretching treatment are as follows: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio is 3-6 times, and stretching rate is 5-30% / s;

[0016] The biaxial solid-phase stretching treatment is synchronous stretching or asynchronous stretching. When it is synchronous stretching, its process parameters are: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio is 3×3-6×6 times, and stretching rate is 5-30% / s; when it is asynchronous stretching, its process parameters are: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio in one stretching direction is 3-6 times, stretching ratio in the other stretching direction is 1-3 times, and stretching rate is 5-30% / s.

[0017] In this article, the Chinese name of PLA in step (1) is polylactic acid, which is a biodegradable material. Conventional industrial PLA raw materials in the field of this technology can be directly selected. Those skilled in the art can select a suitable PLA brand according to specific needs and process requirements, or refer to conventional PLA brands in the application field of the final product, especially PLA raw materials suitable as raw materials for film products in the prior art.

[0018] In one of the technical solutions, the PLA selected in step (1) includes any one of American NatureWorks 4032D, Total L175, Hisun Bio REVODE 110, and Fengyuan FY801 / FY802.

[0019] Herein, the EBH nucleating agent in step (1) is N,N-ethylenebis(12-hydroxystearamide) (EBH), which can be directly obtained from the market by those skilled in the art or synthesized by themselves according to technical literature.

[0020] In one of the technical solutions, the adjuvants conventionally used in PLA processing and molding may be added to the mixture described in step (1) to achieve further functional expansion / process assistance of the product. The specific selection of adjuvants can be referenced by those skilled in the art based on the prior art or existing literature, such as lubricants, flame retardants, antioxidants, heat stabilizers, plasticizers, antibacterial agents and other processing aids / functional aids. It should be noted that the mixture described in step (1) may include or not include adjuvants conventionally used in PLA processing and molding; in the following preferred technical solutions and specific implementations, in order to minimize the influencing factors in the comparative experiment, adjuvants are not added to the mixture, but this does not mean that appropriate adjuvants cannot be added to the mixture. However, it should be noted that the addition of the above-mentioned adjuvants is based on not affecting the transparency of the prepared polylactic acid film. When selecting adjuvants, adjuvants that will not cause dyeing / color difference to the product should be selected, and the total amount of adjuvants added should not exceed 30 parts.

[0021] In this article, the mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing to prepare a sheet to be stretched for film products, wherein screw melt extrusion granulation is a conventional process for making parts using PLA materials, and its specific process steps / process parameters can be directly referred to the prior art records / existing process methods for screw melt extrusion granulation of PLA raw materials.

[0022] In one of the technical solutions, the mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing molding, wherein the screw melt extrusion granulation is processed by a twin-screw extruder, and the specific process parameters are: the temperature from the feed port to the die is in the range of 140 to 200°C, the interval between each screw temperature zone does not exceed 20°C, and the screw speed is 30 to 100 r / min.

[0023] In this article, the mixed material in step (2) is successively subjected to screw melt extrusion granulation and hot pressing molding to prepare a sheet to be stretched for film products, wherein hot pressing molding is a conventional process for making parts using PLA materials, and its specific process steps / process parameters can be directly referred to the existing technical records / existing process methods for hot pressing molding of PLA raw materials.

[0024] In one of the technical solutions, the mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing, wherein the hot pressing is performed using a flat plate vulcanizer, and the specific process parameters are: pressure of 2 to 10 MPa, upper plate temperature of 170 to 220°C, lower plate temperature of 170 to 220°C, preheating for 2 to 10 minutes, hot pressing for 2 to 7 minutes, and cold pressing for 2 to 6 minutes.

[0025] The main invention of the present invention is that, based on the research results of the research group, the inventor of the present invention accidentally discovered that when EBH nucleating agent is selected, under a special solid-phase stretching ratio, the interaction between PLA and EBH nucleating agent can form a unique network crystal structure, giving the film product excellent strength, heat resistance and toughness.

[0026] In the previous research results, the inventor's research group discovered and reported a new strategy of using EBH nucleating agent to effectively regulate the crystallization rate and crystal size of left-handed polylactic acid (PLLA) to obtain high-performance transparent polylactic acid. The results showed that by adding 0.4-0.8wt% EBH nucleating agent to PLLA, highly crystallized (crystallinity as high as 45%) PLLA products can be successfully prepared by melt molding method, which have excellent heat resistance and optical transparency (light transmittance can reach more than 70%).

[0027] Based on the above research results, the inventors of the present invention accidentally discovered that under a special solid-phase stretching ratio, when choosing to use EBH nucleating agent to prepare transparent polylactic acid film products, through the characterization of the cross-sectional electron microscopy observation of the product after etching, the interaction between PLA and EBH nucleating agent formed a unique network crystal structure, which is completely different from the nanofiber network structure formed by self-assembly of EBH nucleating agent small molecules during the melting and cooling process of the matrix in the above research results in terms of principle and characterization, and gives the transparent polylactic acid film products a significant improvement in mechanical properties. In order to better verify the above accidental discovery, in further comparative experiments, on the one hand, it was verified that the above unique network crystal structure can only be well formed under a special solid-phase stretching ratio (3 to 6 times). When the stretching ratio is lower than this, the orientation degree of the polylactic acid molecular chains is low, and they are still randomly arranged and interwoven, and the network crystal structure cannot be obtained. When the stretching ratio is higher than this, the network crystal structure is destroyed to form a unidirectional fiber structure. On the other hand, the comparative experiments confirmed that the above unique network crystal structure only exists in the interaction between PLA and EBH nucleating agent, and when other nucleating agents are used, no consistent or similar network crystal structure is formed.

[0028] Based on the above invention, in order to further improve the performance enhancement brought by the network crystal structure, in one of the more preferred technical solutions, the EBH nucleating agent in step (1) is 1 to 2 parts, and most preferably 1.4 to 1.8 parts.

[0029] It should be noted that when the addition amount of EBH exceeds 4 parts, the transparency of the prepared polylactic acid film will be greatly deteriorated.

[0030] The present invention has the following beneficial effects:

[0031] 1. The present invention provides a transparent polylactic acid film with a network crystal structure and a preparation method thereof. The preparation method selects a specific EBH as a nucleating agent and combines it with a solid-phase stretching technology to prepare a PLA film product with high transparency. It is found that under a special solid-phase stretching ratio, the interaction between PLA and the EBH nucleating agent can form a unique network crystal structure, which gives the film product excellent strength, heat resistance and toughness.

[0032] 2. The preparation method of the technical solution of the present invention is simple and does not require modification of the production equipment. It can be directly implemented in the production process of existing polylactic acid film products, while also bringing about significant performance improvements. It has considerable development and transformation prospects in the field of polymer-based film materials and has good commercial value.

[0033] 3. The present invention provides a transparent polylactic acid film with a network crystal structure and a preparation method thereof. The film uses polylactic acid as the main raw material, does not contain other fillers, has excellent biodegradability, can be directly used as a packaging material, and meets environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The longitudinal section electron microscope micrographs of the comparative sample (left) prepared in comparative example 4 of the present invention and the sample (right) prepared in Example 1 after etching. In the figure, (a) is a longitudinal section electron microscope micrograph of the comparative sample prepared in comparative example 4 after etching, and (b) is a longitudinal section electron microscope micrograph of the sample prepared in Example 1 after etching.

[0035] Figure 2 The mechanical properties comparison bar graphs of the comparative samples prepared in comparative examples 4 to 9 of the present invention and the samples prepared in examples 1 and 3 are shown. In the figure, when the horizontal coordinate of the stretching ratio in (a) is 1, it refers to the comparative sample prepared in comparative example 7, when the horizontal coordinate of the stretching ratio is 2, it refers to the comparative sample prepared in comparative example 6, when the horizontal coordinate of the stretching ratio is 4, it refers to the comparative sample prepared in comparative example 5, and when the horizontal coordinate of the stretching ratio is 6, it refers to the comparative sample prepared in comparative example 4; when the horizontal coordinate of the stretching ratio in (b) is 1, it refers to the comparative sample prepared in comparative example 9, when the horizontal coordinate of the stretching ratio is 2, it refers to the comparative sample prepared in comparative example 8, when the horizontal coordinate of the stretching ratio is 4, it refers to the sample prepared in example 3, and when the horizontal coordinate of the stretching ratio is 6, it refers to the sample prepared in example 1.

[0036] Figure 3The comparative curves of the loss factor and storage modulus of the comparative samples prepared in comparative examples 4 to 9 of the present invention and the samples prepared in Examples 1 and 3 as a function of temperature are shown. In the figure, PLA-1 in (a) refers to the comparative sample prepared in comparative example 7, PLA-2 refers to the comparative sample prepared in comparative example 6, PLA-4 refers to the comparative sample prepared in comparative example 5, and PLA-6 refers to the comparative sample prepared in comparative example 4; PLA-1 in (b) refers to the comparative sample prepared in comparative example 7, PLA-2 refers to the comparative sample prepared in comparative example 6, PLA-4 refers to the comparative sample prepared in comparative example 5, and PLA-6 refers to the comparative sample prepared in comparative example 4; PLA / EBH-1.5wt-1 in (c) refers to the comparative sample prepared in comparative example 9 , PLA / EBH-1.5wt-2 refers to the comparative sample prepared in Comparative Example 8, PLA / EBH-1.5wt-4 refers to the sample prepared in Example 3, and PLA / EBH-1.5wt-6 refers to the sample prepared in Example 1; in (d), PLA / EBH-1.5wt-1 refers to the comparative sample prepared in Comparative Example 9, PLA / EBH-1.5wt-2 refers to the comparative sample prepared in Comparative Example 8, PLA / EBH-1.5wt-4 refers to the sample prepared in Example 3, and PLA / EBH-1.5wt-6 refers to the sample prepared in Example 1.

[0037] Figure 4 The following are photos of the comparative sample prepared in comparative example 4 of the present invention and the sample prepared in Example 1 after being heated in an oven at 80°C for 20 minutes and photos of transparency verification. In the figure, (a) is a photo of the comparative sample prepared in comparative example 4 and the sample prepared in Example 1 being placed in an oven; (b) is a photo of the comparative sample prepared in comparative example 4 after being heated in an oven at 80°C for 20 minutes; (c) is a photo of the sample prepared in Example 1 after being heated in an oven at 80°C for 20 minutes; (d) is a photo of the transparency verification of the sample prepared in Example 1 covered on a pattern.

[0038] Figure 5 The longitudinal section electron microscope micrograph and transparency verification photograph of the comparative sample prepared in comparative example 1 of the present invention after etching. In the figure, (a) is a longitudinal section electron microscope micrograph of the comparative sample prepared in comparative example 1 after etching, and (b) is a transparency verification photograph of the comparative sample prepared in comparative example 1 covered on a pattern.

[0039] Figure 6The mechanical properties comparison column chart of the comparative sample prepared in comparative example 4 of the present invention and the samples prepared in Examples 1 and 2 and the longitudinal section electron microscope micrograph of the sample in Example 2 after etching. In the figure, the left figure is a mechanical properties comparison column chart of the comparative sample prepared in comparative example 4 and the samples prepared in Examples 1 and 2, PLA-6 refers to the comparative sample prepared in comparative example 4, PLA / EBH-1wt-6 refers to the sample prepared in Example 2, and PLA / EBH-1.5wt-6 refers to the sample prepared in Example 1; the right figure is a longitudinal section electron microscope micrograph of the sample prepared in Example 2 after etching. DETAILED DESCRIPTION

[0040] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0041] The present invention provides a method for preparing a transparent polylactic acid film having a network crystal structure, which mainly comprises the following steps:

[0042] (1) The raw materials mainly including the following components are mixed and prepared as a mixed material by weight:

[0043] PLA 95-99.5 parts,

[0044] EBH nucleating agent 0.5-5 parts,

[0045] The polylactic acid and EBH nucleating agent totaled 100 parts;

[0046] (2) subjecting the mixed material prepared in step (1) to melt extrusion granulation and hot pressing molding in sequence to prepare a sheet to be stretched for a film product;

[0047] (3) subjecting the sheet to be stretched obtained in step (2) to uniaxial or biaxial solid phase stretching to prepare a transparent polylactic acid film having a network crystal structure;

[0048] The process parameters of the unidirectional solid phase stretching treatment are as follows: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio is 3-6 times, and stretching rate is 5-30% / s;

[0049] The biaxial solid-phase stretching treatment is synchronous stretching or asynchronous stretching. When it is synchronous stretching, its process parameters are: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio is 3×3-6×6 times, and stretching rate is 5-30% / s; when it is asynchronous stretching, its process parameters are: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio in one stretching direction is 3-6 times, stretching ratio in the other stretching direction is 1-3 times, and stretching rate is 5-30% / s.

[0050] In this article, the Chinese name of PLA in step (1) is polylactic acid, which is a biodegradable material. Conventional industrial PLA raw materials in the field of this technology can be directly selected. Those skilled in the art can select a suitable PLA brand according to specific needs and process requirements, or refer to conventional PLA brands in the application field of the final product, especially PLA raw materials suitable as raw materials for film products in the prior art.

[0051] In one embodiment, the PLA in step (1) is selected from any one of American NatureWorks 4032D, Total L175, Hisun Bio REVODE 110, and Fengyuan FY801 / FY802.

[0052] Herein, the EBH nucleating agent in step (1) is N,N-ethylenebis(12-hydroxystearamide) (EBH), which can be directly obtained from the market by those skilled in the art or synthesized by themselves according to technical literature.

[0053] In one embodiment, the EBH nucleating agent in step (1) is 0.5-5 parts, for example, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2.0 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any range or point value therebetween.

[0054] In one embodiment, the adjuvants conventionally used in PLA processing and molding may be added to the mixture in step (1) to achieve further functional expansion / process assistance of the product. The specific selection of adjuvants can be referenced by those skilled in the art based on the prior art or existing literature, such as lubricants, flame retardants, antioxidants, heat stabilizers, plasticizers, antibacterial agents and other processing aids / functional aids. It should be noted that the mixture in step (1) may include or not include adjuvants conventionally used in PLA processing and molding; in the following preferred technical solutions and specific embodiments, in order to minimize the influencing factors in the comparative experiment, adjuvants are not added to the mixture, but this does not mean that appropriate adjuvants cannot be added to the mixture. However, it should be noted that the addition of the above-mentioned adjuvants is based on not affecting the transparency of the prepared polylactic acid film. When selecting adjuvants, adjuvants that will not cause dyeing / color difference to the product should be selected, and the total amount of adjuvants added should not exceed 30 parts.

[0055] In this article, the mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing to prepare a sheet to be stretched for film products, wherein screw melt extrusion granulation is a conventional process for making parts using PLA materials, and its specific process steps / process parameters can be directly referred to the prior art records / existing process methods for screw melt extrusion granulation of PLA raw materials.

[0056] In one embodiment, the mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing molding, wherein the screw melt extrusion granulation is processed by a twin-screw extruder, and the specific process parameters are: the temperature from the feed port to the die is in the range of 140 to 200°C, the interval between each screw temperature zone does not exceed 20°C, and the screw speed is 30 to 100 r / min.

[0057] In this article, the mixed material in step (2) is successively subjected to screw melt extrusion granulation and hot pressing molding to prepare a sheet to be stretched for film products, wherein hot pressing molding is a conventional process for making parts using PLA materials, and its specific process steps / process parameters can be directly referred to the existing technical records / existing process methods for hot pressing molding of PLA raw materials.

[0058] In one embodiment, the mixture in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing, wherein the hot pressing is performed using a flat plate vulcanizer, and the specific process parameters are: pressure of 2 to 10 MPa, upper plate temperature of 170 to 220°C, lower plate temperature of 170 to 220°C, preheating for 2 to 10 minutes, hot pressing for 2 to 7 minutes, and cold pressing for 2 to 6 minutes.

[0059] In one embodiment, the stretching temperature in step (3) is 70-120°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any range or point value therebetween; the preheating time is 5-120s, for example, 5s, 10s, 15s, 20s, 25s, 30s, 35s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 120s or any range or point value therebetween; the stretching ratio is 3-6 times, for example, 3 times, 3.5 times s, 4 times, 4.5 times, 5 times, 5.5 times, 6 times or any range or point value therebetween; the stretching rate is 5 to 30% / s, for example 5% / s, 6% / s, 7% / s, 8% / s, 9% / s, 10% / s, 11% / s, 12% / s, 13% / s, 14% / s, 15% / s, 16% / s, 17% / s, 18% / s, 19% / s, 20% / s, 21% / s, 22% / s, 23% / s, 24% / s, 25% / s, 26% / s, 27% / s, 28% / s, 29% / s, 30% / s or any range or point value therebetween.

[0060] The main invention of the present invention is that, based on the research results of the research group, the inventor of the present invention accidentally discovered that when EBH nucleating agent is selected, under a special solid-phase stretching ratio, the interaction between PLA and EBH nucleating agent can form a unique network crystal structure, giving the film product excellent strength, heat resistance and toughness.

[0061] In the previous research results, the inventor's research group discovered and reported a new strategy of using EBH nucleating agent to effectively regulate the crystallization rate and crystal size of left-handed polylactic acid (PLLA) to obtain high-performance transparent polylactic acid. The results showed that by adding 0.4-0.8wt% EBH nucleating agent to PLLA, highly crystallized (crystallinity as high as 45%) PLLA products can be successfully prepared by melt molding method, which have excellent heat resistance and optical transparency (light transmittance can reach more than 70%).

[0062] Based on the above research results, the inventors of the present invention accidentally discovered that under a special solid-phase stretching ratio, when choosing to use EBH nucleating agent to prepare transparent polylactic acid film products, through the characterization of the cross-sectional electron microscopy observation of the product after etching, the interaction between PLA and EBH nucleating agent formed a unique network crystal structure, which is completely different from the nanofiber network structure formed by self-assembly of EBH nucleating agent small molecules during the melting and cooling process of the matrix in the above research results in terms of principle and characterization, and gives the transparent polylactic acid film products a significant improvement in mechanical properties. In order to better verify the above accidental discovery, in further comparative experiments, on the one hand, it was verified that the above unique network crystal structure can only be well formed under a special solid-phase stretching ratio (3 to 6 times). When the stretching ratio is lower than this, the orientation degree of the polylactic acid molecular chains is low, and they are still randomly arranged and interwoven, and the network crystal structure cannot be obtained. When the stretching ratio is higher than this, the network crystal structure is destroyed to form a unidirectional fiber structure. On the other hand, the comparative experiments confirmed that the above unique network crystal structure only exists in the interaction between PLA and EBH nucleating agent, and when other nucleating agents are used, no consistent or similar network crystal structure is formed.

[0063] Based on the above invention, in order to further improve the performance enhancement brought by the network crystal structure, in one of the more preferred technical solutions, the EBH nucleating agent in step (1) is 1 to 2 parts, and most preferably 1.4 to 1.8 parts.

[0064] It should be noted that when the addition amount of EBH exceeds 4 parts, the transparency of the prepared polylactic acid film will be greatly deteriorated.

[0065] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0066] Example

[0067] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0068] 1. Raw materials

[0069] PLA: Fengyuan FY801 pellets;

[0070] EBH nucleating agent: Jiangxi Dongyuan Technology Co., Ltd.

[0071] TMC nucleating agent, TMC-300.

[0072] 2. Test Method

[0073] 1) Tensile performance test

[0074] The extended section of the specimen after solid phase stretching is cut into a suitable length, and then the two ends are clamped together with the original unstretched specimen using the tensile test fixture of the electronic universal material testing machine, leaving 25mm in the middle as the test section, and then the tensile performance test is carried out at a speed of 5mm / min.

[0075] 2) Scanning electron microscope test (SEM):

[0076] The spline to be observed is cut along the stretching direction to obtain a thin slice of the longitudinal section of the spline, which is then placed in a methanol / water solution containing sodium hydroxide for etching to remove the amorphous phase. Finally, it is placed on a test bench, and after gold spraying treatment, it is observed and photographed using a scanning electron microscope to obtain an electron microscope microscopic image of the longitudinal section.

[0077] 3) Thermal performance test (DMA):

[0078] The extended section of the specimen after solid phase stretching is cut into appropriate lengths and placed in the fixtures at both ends of the machine, with 8-10mm reserved in the middle as the test section. The temperature is raised from 40℃ to 120℃ at 3℃ / min, and the frequency and amplitude are fixed at 1Hz and 10μm respectively.

[0079] 3. Preparation method

[0080] (1) The raw materials mainly including the following components are mixed and prepared as a mixed material by weight:

[0081] PLA 95-99.5 parts,

[0082] EBH nucleating agent 0.5-5 parts,

[0083] The polylactic acid and EBH nucleating agent totaled 100 parts;

[0084] (2) subjecting the mixed material prepared in step (1) to melt extrusion granulation and hot pressing molding in sequence to prepare a sheet to be stretched for a film product;

[0085] Among them, the screw melt extrusion granulation is processed by a twin-screw extruder, and the specific process parameters are: the temperature from the feed port to the die is 140°C, 160°C, 170°C, 180°C, 180°C, 180°C, 185°C, 185°C, 185°C, 180°C, 180°C, and the screw speed is 60r / min;

[0086] The hot pressing molding is processed by a flat plate vulcanizing machine, and the specific process parameters are: pressure 10MPa, upper plate temperature 190℃, lower plate temperature 190℃, preheating for 6min, hot pressing for 5min, cold pressing for 4min;

[0087] (3) subjecting the sheet to be stretched obtained in step (2) to uniaxial solid phase stretching treatment to prepare a transparent polylactic acid film with a thickness of 200 μm and a network crystal structure;

[0088] The process parameters of the unidirectional solid phase stretching treatment are as follows: stretching temperature is 90° C., preheating time is 20 s, stretching ratio is 4 to 6 times, and stretching rate is 15% / s.

[0089] Example 1

[0090] Example 1 is a transparent polylactic acid film with a network crystal structure prepared as a sample according to the above "3. Preparation method", wherein the addition amount of EBH nucleating agent is 1.5 parts, and the stretching ratio is 6 times.

[0091] Example 2

[0092] Example 2 is a transparent polylactic acid film with a network crystal structure prepared as a sample according to the above "3. Preparation method", wherein the added amount of EBH nucleating agent is 1 part and the stretching ratio is 6 times.

[0093] Example 3

[0094] Example 3 is a transparent polylactic acid film with a network crystal structure prepared as a sample according to the above "3. Preparation method", wherein the addition amount of EBH nucleating agent is 1.5 parts, and the stretching ratio is 4 times.

[0095] Example 4

[0096] Example 4 is a transparent polylactic acid film with a network crystal structure prepared as a sample according to the above "3. Preparation method", wherein the added amount of EBH nucleating agent is 1 part and the stretching ratio is 4 times.

[0097] Comparative Example 1

[0098] Comparative Example 1 is a polylactic acid film prepared according to the above "3. Preparation method" as a comparative sample, but the EBH nucleating agent is replaced by a TMC nucleating agent (octamethylene dicarboxylic acid dibenzoyl hydrazide, TMC-300), and the added amount is 1.5 parts, and the stretching ratio is 6 times.

[0099] Comparative Example 2

[0100] Comparative Example 2 is a polylactic acid film prepared according to the above “3. Preparation method” as a comparative sample, but the EBH nucleating agent is replaced by carbon nanotubes, and the added amount is 1.5 parts, and the stretching ratio is 6 times.

[0101] Comparative Example 3

[0102] Comparative Example 3 is a polylactic acid film prepared according to the above “3. Preparation method” as a comparative sample, but the EBH nucleating agent is replaced by talcum powder, and the added amount is 1.5 parts, and the stretching ratio is 6 times.

[0103] Comparative Example 4

[0104] Comparative Example 4 is a polylactic acid film prepared according to the above “3. Preparation method” as a comparative sample, but without adding the EBH nucleating agent, that is, the amount of polylactic acid added is 100 parts, and the stretching ratio is 6 times.

[0105] Comparative Example 5

[0106] Comparative Example 5 is a polylactic acid film prepared according to the above “3. Preparation method” as a comparative sample, but without adding the EBH nucleating agent, that is, the addition amount of polylactic acid is 100 parts, and the stretching ratio is 4 times.

[0107] Comparative Example 6

[0108] Comparative Example 6 is a polylactic acid film prepared according to the above “3. Preparation method” as a comparative sample, but without adding the EBH nucleating agent, that is, the addition amount of polylactic acid is 100 parts, and the stretching ratio is 2 times.

[0109] Comparative Example 7

[0110] Comparative Example 7 is a polylactic acid sheet prepared according to the above "3. Preparation method" as a comparison sample, but no EBH nucleating agent is added, that is, the amount of polylactic acid added is 100 parts, and the unidirectional solid phase stretching treatment in step (3) is not performed. The sheet to be stretched obtained in step (2) is directly tested as a comparison sample.

[0111] Comparative Example 8

[0112] Comparative Example 8 is a polylactic acid film prepared according to the above “3. Preparation method” as a comparative sample, wherein the addition amount of EBH nucleating agent is 1.5 parts, but the stretching ratio is 2 times.

[0113] Comparative Example 9

[0114] Comparative Example 9 is a polylactic acid sheet prepared according to the above "3. Preparation method", wherein the amount of EBH nucleating agent added is 1.5 parts, but the unidirectional solid phase stretching treatment in step (3) is not implemented, and the sheet to be stretched obtained in step (2) is directly tested as a comparison sample.

[0115] 4. Test Results

[0116] Test results such as Figures 1 to 6 As shown:

[0117] from Figure 1 It is obvious that the crystals of the comparison sample composed of pure PLA are clearly oriented along the stretching direction to form a fibrous crystal structure. After adding the EBH nucleating agent, the crystal structure changes significantly under the joint action of PLA and EBH nucleating agent, forming a network crystal structure, which plays a role of physical cross-linking.

[0118] from Figure 2 It is obvious that under the same stretching ratio, the mechanical strength and elongation at break of the sample with the addition of EBH nucleating agent are higher than those of pure PLA, especially when the stretching ratio is 6 times, the tensile strength and elongation at break of the sample show a significant increase, reaching 112MPa and 63% respectively, compared with the control samples with the same stretching ratio, the increases are 53.4% ​​and 117% respectively.

[0119] exist Figure 3 (a) is a comparison curve of the loss factor of the comparative sample at different stretching ratios versus temperature, and the glass transition temperature (T g ) is about 66.2℃; and as the stretching ratio increases, T g When the stretching ratio is 6, the T g Increased to 79.9℃, an increase of 13.7℃. (b) The figure is a comparison curve of the storage modulus of the comparative samples at different stretching ratios with temperature. The storage modulus of the comparative samples without solid phase stretching treatment and with a stretching ratio of 2 times decreases rapidly at around 60℃. At 80℃, it is only about 4MPa and 10MPa, respectively, indicating that the comparative samples have undergone serious thermal deformation at this temperature; as the temperature further increases, the comparative samples without solid phase stretching treatment and with a stretching ratio of 2 times undergo cold crystallization, and the storage modulus increases instead, but the comparative samples become opaque due to cold crystallization; when the stretching ratio is increased to 4 times, the thermal deformation of the sample at 80℃ is suppressed, the storage modulus increases to 300MPa, and no cold crystallization occurs, and the comparative samples still maintain good transparency; when the stretching ratio is further increased to 6 times, the storage modulus of the comparative sample at 80℃ is greatly increased to 1500MPa, and even at 110℃, the storage modulus of the comparative sample is still 220MPa. (c) is a comparison curve of the loss factor of the sample with EBH nucleating agent added and the control sample at different stretching ratios. It is obvious that when no solid phase stretching treatment is performed, the control sample undergoes severe thermal deformation at 80°C, and cold crystallization also occurs as the temperature rises; when the stretching ratio is increased to 6 times, the T gIt increases to 84.4℃, which is 4.5℃ higher than the pure PLA control sample with the same stretching ratio. And it can be seen from Figure (d) that the storage modulus of the sample at 110℃ is 350MPa, which is much higher than the pure PLA control sample with the same stretching ratio (220MPa), indicating that the heat resistance of the film product is further improved after the addition of EBH nucleating agent.

[0120] from Figure 4 It is obvious that under the same weight, the comparative sample prepared in Comparative Example 4 is severely deformed, while the sample prepared in Example 1 is almost not deformed. In addition, the sample prepared in Example 1 has excellent transparency.

[0121] like Figure 5 As shown in the figure, after replacing the EBH nucleating agent with the TMC nucleating agent, the comparative sample prepared according to the same embodiment did not form a mesh crystal structure, but formed fibers along the stretching direction. In addition, the light transmittance of the product was very poor. The same characteristic phenomenon also occurred in the comparative samples prepared in Comparative Examples 2 and 3, which fully proved the necessity of adding the EBH nucleating agent.

[0122] from Figure 6 It is obvious that when Example 2 adds 1wt% EBH nucleating agent, its tensile strength only increases from 73MPa of pure PLA in Comparative Example 4 to 84MPa, but is much lower than the sample in Example 1 (112MPa) with the same 6-fold stretching ratio. Through etching electron microscopy observation, it is found that although the sample in Example 2 forms a certain network crystal structure, its network density is much lower than Figure 1 The mechanical properties of the sample in Example 1, which has the same stretching ratio of 6 times, are also much lower than those of the sample in Example 1.

[0123] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a transparent polylactic acid film having a network crystal structure, characterized in that The main steps include: (1) The raw materials mainly including the following components are mixed and prepared as a mixed material by weight: PLA 95-99.5 parts, EBH nucleating agent 0.5-5 parts, The polylactic acid and EBH nucleating agent totaled 100 parts; (2) subjecting the mixed material prepared in step (1) to melt extrusion granulation and hot pressing molding in sequence to prepare a sheet to be stretched for a film product; (3) subjecting the sheet to be stretched obtained in step (2) to uniaxial or biaxial solid phase stretching to prepare a transparent polylactic acid film having a network crystal structure; The process parameters of the unidirectional solid phase stretching treatment are as follows: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio is 3-6 times, and stretching rate is 5-30% / s; The biaxial solid-phase stretching treatment is synchronous stretching or asynchronous stretching. When it is synchronous stretching, its process parameters are: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio is 3×3-6×6 times, and stretching rate is 5-30% / s; when it is asynchronous stretching, its process parameters are: stretching temperature is 70-120°C, preheating time is 5-120s, stretching ratio in one stretching direction is 3-6 times, stretching ratio in the other stretching direction is 1-3 times, and stretching rate is 5-30% / s.

2. The preparation method according to claim 1, characterized in that: The mixture in step (1) also includes auxiliary agents conventionally used in PLA processing and molding.

3. The preparation method according to claim 2, characterized in that: The total amount of additives added is not more than 30 parts.

4. The preparation method according to claim 1, characterized in that: The mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing molding, wherein the screw melt extrusion granulation is processed by a twin-screw extruder, and the specific process parameters are: the temperature from the feed port to the die is in the range of 140 to 220°C, and the screw speed is 30 to 100 r / min.

5. The preparation method according to claim 1, characterized in that: The mixed material in step (2) is sequentially subjected to screw melt extrusion granulation and hot pressing molding, wherein the hot pressing molding is carried out using a flat plate vulcanizer, and the specific process parameters are: pressure of 2 to 10 MPa, upper plate temperature of 170 to 220° C., lower plate temperature of 170 to 220° C., preheating for 2 to 10 minutes, hot pressing for 2 to 7 minutes, and cold pressing for 2 to 6 minutes.

6. The preparation method according to claim 1, characterized in that: The EBH nucleating agent in step (1) is 1 to 2 parts.

7. A transparent polylactic acid film prepared by the method for preparing a transparent polylactic acid film having a three-dimensional crystal network structure as claimed in claim 1.

8. Use of the transparent polylactic acid film as claimed in claim 8 as packaging material.

Citation Information

Patent Citations

  • High-transparency and high-heat-resistance polylactic acid material or product and preparation method thereof

    CN112920574A

  • One-way and two-way solid-phase stretching processing method of regenerated mixed plastic material

    CN114907600A

  • High-temperature-resistant polylactic acid two-way stretch film and preparation method thereof

    CN117464947A

  • High-performance biaxial orientation polypropylene-based capacitor film and preparation method and application thereof

    CN118206787A

  • Polylactic acid-polyalkylene glycol copolymer with fast crystallization rate and composition comprising the same

    KR1020150086073A